Career Advancement for Women in the British Hospitality Industry: The Enabling Factors. (August 2021) - Calinaud, Valentine; Kokkranikal, Jithendran; Gebbels, Maria
Women are historically under-represented in senior management positions in almost all industries. Despite the UK hospitality industry being a major employer of women, there is a clear lack of women in management positions. This research aims to gain insight into the factors enabling women to access senior positions in the UK hospitality industry. Using the gendered organizations perspective, the study analyses female managers' perceptions about their career advancement within this sector. It identifies key enablers and strategies to facilitate women's career advancement. The findings reveal that despite improvements in career opportunities for women within the UK hospitality organizations, there is still a long way to go in terms of employment policies and practices that enable women's career progression, which includes family-friendly practices; proactive and transparent gender equality measures; support networks and mentors; and personal development plan.